Exploring Pakistani Undergraduate Medical Students, Preferences: A Comparative Analysis of Problem Based Learning vs Lecture Based Learning - Noor, Sheh; Ibrahim, Maryam; Qaddus, Attia; Ghazal, Irsa; Ali, Urooj (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To investigate and compare the preferences of Pakistani undergraduate medical students regarding problem-based learning and lecture-based learning. Methods This was a cross-sectional comparative analysis employed with an online Google Docs questionnaire distributed to Pakistani medical students via social media platforms. Utilizing a non-probability convenience sampling technique, participants were enrolled in data collection. Results Among the 200 respondents, 29% were from the final year, while 8%,27.5%,26.5%, and 9% were from fourth, third, second, and first professional, respectively. Problem-based learning was favored by 68% of learners and only 32% of students liked lecture-based learning. It was found that 71% of participants expressed the view that PBL resulted in an enhanced understanding of lecture content. As reported by 73.5% of participants, PBL leads to the improvement of the habit of self-learning. Furthermore, 78% of students claimed that PBL leads to a better analytical approach toward problem-solving. In terms of pre-session preparation, 65.5% and in terms of developing competencies 82.5% of students claimed the superiority of PBL over LBL. Regarding the accessibility of resources for facilitating PBL sessions, only 49% of students expressed satisfaction, while 58.5% of the respondents admitted the availability of trained demonstrators for LBL sessions. Conclusion The results of this study demonstrate that PBL outperforms LBL in enhancing student competencies. Moreover, these findings indicate a strong preference among students for PBL over LBL. However, it is crucial to address the pressing need for enhancing resources dedicated to conducting PBL sessions.